The role of Lactobacillus acidophilus LA-5 and Bifidobacterium lactis BB12 in improving some characteristics of fermented banana puree - Abdullah Awad; Amer Al-Zobaay (Kufa Journal for Agricultural Sciences)
Green banana puree was fermented using a combination of single and mixed probiotic cultures of Lactobacillus acidophilus LA-5 and Bifidobacterium lactis BB12 by seven different treatments. All treatments showed statistically significant differences during the two fermentation periods (24 and 48 hours) in terms of the viability of probiotics, pH and sensory evaluation. It was found that the 48-hour period of fermentation is better than the 24-hour period in improving the quality and properties of fermented bananas. Treatment (Tre.5) which included a mixed probiotic culture prepared in a ratio of (50:50), obtained the highest viability of probiotics as reached 11.37 log CFU/g, an appropriate pH which reached 3.42, better sensory acceptance which reached 86% as compared to other treatments, and sufficient level of anti-bacterial activity against some species of pathogenic and undesirable bacteria.